ETHNOBOTANICAL STUDY ON MEDICINAL PLANTS USED BY THE LOCAL COMMUNITIES IN ACHANAKMAR AMARKANTAK BIOSPHERE RESERVE, CENTRAL INDIA - Mishra, Alka; Parihar, Nisha; Swamy, S (MATTER: International Journal of Science and Technology, 2017)
An ethno-botanical survey was conducted in Achanakmar Amarkantak Biosphere Reserve (AABR) of central India to document the indigenous knowledge and utilization pattern of medicinal plants for primary health care by local communities mainly comprised of Baigas, Gonds, Oraons and Pradhans. The communities still rely on herbal medicines for primary health care due to inadequate modern health care facilities. The rich wealth of traditional knowledge and repository of herbal resources are rapidly eroding due to over exploitation in unscientific manner over the last few decades. This has spurred an interest to undertake the present investigation on ethno botanical studies in biosphere reserve. Data collection was done by participatory rural appraisal (PRA) and focus group discussion methods. The different age groups, gender and communities were considered in collecting the data and gathering information on traditional knowledge. The study revealed that a sum total of 70 plants representing 37 families were identified as potential medicinal values by local communities. Out of which 31species were trees represented by18 families, 24 species of shrubs by19 families, 15 species of herbs by 11 families and 16 species of climbers belonging 10 families. The highest number individuals were recorded in Fabaceae family.Seventeen (17) plants are used in home remedies by local communities.There are traditional healers popularly known as Baiga Vaids had rich knowledge of herbal medicines and utilizing almost 48 species belonging to 28 families for preparing crude drugs treating the various ailments like diarrhoea, wounds, fever, cough, cold, jaundice, snake and scorpion bite, infections, malaria, filarial, digestive, gynaecological problems etc. Besides, the local communities were using herbal drugs as home remedies for primary health problems. The study also documented a list of ten rare, endangered and threatened (RET) medicinal flora, which require special attention for their protection and conservation. The study further suggests exploiting potential medicinal flora by detailed pharmacological investigations to design and synthesize novel drugs.